5-ALA Mediated Fluorescence Detection of Gastrointestinal Tumors. (27th July 2008) - Borisova, Ekaterina; Vladimirov, Borislav; Avramov, Latchezar
Abstract : Delta-aminolevulinic acid/protoporphyrin IX is applied for fluorescent tumor detection in the upper part of gastrointestinal tract. The 5-ALA is administered per os six hours before measurements at dose 20 mg/kg weight. High-power light-emitting diode at 405 nm is used as an excitation source. Special opto-mechanical device is built to use the light guide of standard video-endoscopic system. Through endoscopic instrumental channel a fiber is applied to return information about fluorescence to microspectrometer. In such way, 1D detection and 2D visualization of the lesions' fluorescence are received, and both advantages and limitations of these methodologies are discussed in relation to their clinical applicability. Comparison of the spectra received from normal mucosa, inflammatory, and tumor areas is applied to evaluate the feasibility for development of simple but effective algorithm based on dimensionless ratio of the fluorescence signals at 560 and 635 nm, for differentiation of normal/abnormal gastrointestinal tissues.